José Augusto Pereira Barreiros (1977–2007) - Bonaldo, Alexandre B.; Brescovit, Antonio D.; Pinto-Da-Rocha, Ricardo; Rheims, Cristina A. (Zootaxa, 2007)
Guto’s interest in the study of arachnids began in 2000 when, as an undergraduate student, he joined the staff of the recently established Arachnology Laboratory at the Museu Paraense Emílio Goeldi in Belém, Brazil. He graduated a year later from the Universidade Federal do Pará (UFPA), and presented, as a final monograph, a structured inventory of the soil spider fauna from an urban park in the city of Belém, in which he compared the efficiency of three sampling techniques. His interest in soil spiders lead him to propose, as an M.Sc. dissertation project, a comprehensive structured inventory of soil spiders of the Ferreira Penna Scientific Station, in the Caxiuanã National Forest, Eastern Amazonia. Shortly after he obtained his M.Sc. in 2004, he commenced his Ph.D. research, dealing with community ecology of both soil and arboreal spiders in Caxiuanã. In the first two years of his Ph.D. project he completed the most intensive collecting program of spiders ever carried out in a single locality in Eastern Amazonia, applying a sampling protocol composed of several collecting techniques